2019
DOI: 10.15252/emmm.201910360
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress at the crossroads of progeria and atherosclerosis

Abstract: Hutchinson–Gilford progeria syndrome ( HGPS ) is a rare pathology caused by a specific mutation ( c .1824C>T; p .G608G) in the LMNA gene (Eriksson et al , 2003 ). In healthy conditions, LMNA encodes lamins A and C, two major structural nuclear proteins. The mutation creates a splice site in exon 11, resulting in ubiquitous expression of progeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…A great deal of research indicates that ER stress occurs in a variety of cell types involved in AS including endothelial cells and macrophages and also influences the disease process of AS by coordinating protein and lipid metabolism, inflammatory response, various stress responses, and cell death [13, 7278]. Similarly, the NLRP3 inflammasome and its genetic variants are involved in atherosclerotic pathogenesis [79, 80].…”
Section: The Molecular Pathways Between Er Stress and Nlrp3 Inflammentioning
confidence: 99%
“…A great deal of research indicates that ER stress occurs in a variety of cell types involved in AS including endothelial cells and macrophages and also influences the disease process of AS by coordinating protein and lipid metabolism, inflammatory response, various stress responses, and cell death [13, 7278]. Similarly, the NLRP3 inflammasome and its genetic variants are involved in atherosclerotic pathogenesis [79, 80].…”
Section: The Molecular Pathways Between Er Stress and Nlrp3 Inflammentioning
confidence: 99%
“…ER stress, oxidative stress, and inflammatory response together make up defense networks of the cells that react to outside stimuli [ 8 , 61 ]. Risk factors related to AS, such as hyperlipidemia, hypertension, and obesity, activated the ER stress-related proteins, such as IRE1, PERK, and ATF6, and aggravated the inflammatory response in macrophages [ 62 , 63 ]. UPR activation and ER stress had been identified in atherosclerotic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…A number of scientists have identified a relationship between endoplasmic reticulum stress and the occurrence of atherosclerosis [ 222 , 223 , 224 , 225 , 226 , 227 ]. It was found that ER stress occurs in cells involved in the occurrence and development of atherosclerosis, including endothelial cells and macrophages.…”
Section: The Relationship Of Chronic Stress With the Occurrence Anmentioning
confidence: 99%